2020
DOI: 10.1016/j.cherd.2020.05.025
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and computational study of the flow characteristics in a Type B aortic dissection: Effect of primary and secondary tear size

Abstract: Aortic dissection is related to the separation of the tunica intima from the aortic wall, which can cause blood to flow through the newly formed lumen, thereby further damaging the torn vessel. This type of pathology is the most common catastrophic event that affects the aorta and is associated with complications such as malperfusion. In this work, an idealised, simplified geometric model of Type B aortic dissection is investigated experimentally using particle image velocimetry (PIV) and numerically using com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…22 PIV was recently used to study the impact of tear size on the flow in an idealised model of AD using computations and experiments. 30 However, to date, PIV has not been used in any patient-specific in vitro AD work.…”
Section: Introductionmentioning
confidence: 99%
“…22 PIV was recently used to study the impact of tear size on the flow in an idealised model of AD using computations and experiments. 30 However, to date, PIV has not been used in any patient-specific in vitro AD work.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these, AD benchtop experiments – either employing an ex-vivo vessel or a synthetic replica – started to be employed and allowed the study of haemodynamic variables through different measurement techniques (e.g. Ultrasound (US) Chung et al, 2000a , magnetic resonance imaging (MRI) Birjiniuk et al, 2017 and, only recently, Particle Image Velocimetry (PIV) Zadrazil et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parametric studies with idealised artificial phantoms have increased the understanding of the pathology and have highlighted the importance of morphological features on the haemodynamic variables ( Chung et al, 2000b , Rudenick et al, 2013 , Marconi et al, 2017 , Zadrazil et al, 2020 ) ( Table 1 ). Parametric studies can also be used to assess possible treatment methods and their impact on parameters of interest (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A haemodynamic study was also conducted within an in vitro patient-specific Type B aortic dissection phantom model under steady ( 14 ) and pulsatile ( 15 ) flow conditions with undocumented stiffness or compliance values. Zadrazil et al ( 16 ) performed steady flow computational and experimental simulations on an idealised Type B aortic dissection without branching vessels. Patient-specific computational studies incorporating branching vessels along a Type B dissection have previously been reported ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%